Unveiling Students’ Perceptions of Project-Based Learning (PjBL): Insights from Sociolinguistics Class - Patmasari, Andi; Muhammad Ismail; Abdul Kamaruddin; Misnariah Idrus; Aisah Apridayani (Journal of Learning Improvement and Lesson Study, 2025)
Students’ perception has an important role in the success of the learning process. Therefore, the objective of this research was to investigate and describe the students’ perception of PjBL in Sociolinguistics class. This research applied descriptive qualitative. Sources of data or research respondents were the students of English Education Study Program of Tadulako University who enrolled in Sociolinguistics in Educational Context class, especially the ones in classes E and F. The researchers used questionnaire and interview to get relevant and accurate information or data. The researchers analysed data through three stages: data reduction, data display, and conclusion. Based on the questionnaire and interview, it can be seen that most students gave positive responses to implementation of PjBL. They stated that PjBL widens their understanding of Sociolinguistics and develops their problem-solving, communication, critical thinking, and decision-making skills. The research findings can enrich the knowledge about the learning model, the mechanism of providing a project, and the stages that must be followed. And also students’ perception of PjBL could describe the implementation of the learning model that could be considered by lecturers or teachers in managing classes, selecting projects, and choosing the best learning model.